Simbol Lokal dalam Lagu Karya Didi Kempot: Analisis Semiotika - Ayunda Putri Nazarrina; Dzarna Dzarna; Yerry Mijianti (JENTERA: Jurnal Kajian Sastra, 2025)
This study aims to analyze the denotative, connotative, and mythological meanings of local symbols in Didi Kempot's song lyrics using Roland Barthes' semiotic approach. The method used is descriptive qualitative with a focus on interpreting the meaning of the lyric text. Data collection techniques were carried out through documentation of song lyrics containing local symbols such as Stasiun Balapan, Cidro, Suket Teki, Sewu Kuto, and Pamer Bojo, as well as literature studies from scientific sources relevant to Javanese culture and semiotic theory. The analysis was carried out by tracing linguistic elements in the lyric text that function as symbols of Javanese culture through Barthes's three levels of meaning: denotation (literal meaning), connotation (emotional and cultural meaning), and myth (ideological meaning). The results of the study show that at the denotative level, the symbols depict concrete objects such as stations, terminals, and traditional foods. At the connotative level, these symbols contain emotional meanings related to separation, betrayal, and life's struggles. Meanwhile, at the mythical level, these symbols reflect the Javanese people's view of life, which is receptive, patient, and upholds human values. Abstrak Penelitian ini bertujuan menganalisis makna denotatif, konotatif, dan mitologis dari simbol-simbol lokal dalam lirik lagu Didi Kempot menggunakan pendekatan semiotika Roland Barthes. Metode yang digunakan adalah kualitatif deskriptif dengan fokus pada penafsiran makna teks lirik. Teknik pengumpulan data dilakukan melalui dokumentasi lirik lagu yang mengandung simbol lokal seperti Stasiun Balapan, Cidro, Suket Teki, Sewu Kuto, dan Pamer Bojo, serta studi kepustakaan dari sumber-sumber ilmiah yang relevan dengan budaya Jawa dan teori semiotika. Analisis dilakukan dengan menelusuri unsur linguistik dalam teks lirik yang berfungsi sebagai simbol budaya Jawa melalui tiga tingkatan makna Barthes: denotasi (makna literal), konotasi (makna emosional dan kultural), dan mitos (makna ideologis). Hasil penelitian menunjukkan bahwa pada tingkat denotatif, simbol-simbol tersebut menggambarkan objek konkret seperti stasiun, terminal, dan makanan tradisional. Pada tingkat konotatif, simbol-simbol ini mengandung makna emosional yang berkaitan dengan perpisahan, pengkhianatan, dan perjuangan hidup. Sedangkan pada tingkat mitos, simbol-simbol tersebut merefleksikan pandangan hidup masyarakat Jawa yang nrimo, sabar, dan menjunjung tinggi nilai kemanusiaan.